Cardiac amyloidosis. (February 2014) - Yusuf, Syed Wamique; Solhpour, Amirreza; Banchs, Jose; Lopez-Mattei, Juan C; Durand, Jean-Bernard; Iliescu, Cezar; Hassan, Saamir A; Qazilbash, Muzaffar H
<x xml:space="preserve">Abstract</x> Amyloidosis is a condition characterized by the extracellular deposition of insoluble fibrillar protein in tissues and various organs including the heart. This review summarizes the clinical manifestations, diagnostic and treatment approaches for cardiac amyloidosis.